Work From Home or Bring Home the Work? Burnout and Procrastination in Brazilian Workers During the COVID-19 Pandemic. Issue 5 (24th May 2022) - Arenas, Daniel Luccas; Viduani, Anna; Bassols, Ana Margareth Siqueira; Hauck, Simone
Abstract : This cross-sectional study highlights that working from home (WFH) may have more advantages than disadvantages in ideal conditions during the COVID-19 pandemic. However, work-life imbalances and social and gender inequalities seem to be key aspects regarding distress and burnout among workers WFH, especially in women with small children. Abstract : Objective: To investigate burnout and procrastination in a sample of Brazilian workers during the COVID-19 pandemic according to their current work mode. Methods: This cross-sectional study used data from an online survey conducted in 2020: 435 workers were included. The Copenhagen Burnout Inventory and the Irrational Procrastination Scale were used to access burnout and procrastination respectively. Results: There was no difference between workers working from home (WFH) and at face-to-face work regarding burnout symptoms. However, the WFH group had higher levels of procrastination. Clinically significant levels of burnout were associated with being female, increased childcare load and living with children under 12years old. Conclusions: WFH may have more advantages than disadvantages in ideal conditions. However, work-life imbalances seem to be a key aspect regarding distress among workers WFH, especially in women with small children.